PENGARUH MODEL PEMBELAJARAN PICTURE AND PICTURE BERBANTUAN FLASH CARD TERHAADAP PEMAHAMAN KONSEP RANTAI MAKANAN PADA SISWA KELAS V SDN 2 SUKOREJO - Ayu Lestari; Ela Suryani (JANACITTA, 2022)
Abstract ABSTRAKThis study aims to determine the effect of the flash card assisted picture and1 picture learning model on the understanding of the concept of the student food chain. The design of this study isquasiexperimental, non-equivalent control group design. Samples were taken by purposive sampling and obtained class 5A as an experimental class and class 5B as a control class at SDN 2 Sukorejo. Data collection techniques used in this research are observation, interview, and documentation. Data analysis techniques in this study are normality test, homogeneity test. Independent sampet-test and simple linear regeression test. The results showed : 1) there are differences in the learning model of picture and picture assisted flash card to the understanding of the concept of the food chain of students with a significant value of 0.016<0.05 and 0.015<0.05; 2) there is an effect of using the learning model of picture and picture assisted flash card to the understanding of the concept of the food chain of students with a significance level of 0.006 < 0.05. So it can be concluded that the learning model of picture and picture assisted flash card affects the understanding of the concept of the food chain.Keywords : flash card, concept understanding, picture and picture.ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran picture and picture berbantuan flash card terhadap pemahaman konsep rantai makanan siswa. Desain penelitian ini adalah quasi exsperimen, non-equivalent control group design. Sampel diambil secara purposive sampling dan didapatkan kelas 5A sebagai kelas eksperimen dan kelas 5B sebagai kelas kontrol di SDN 2 Sukorejo. Teknik pengumpulan data ini menggunakan observasi, wawancara dan tes. Teknik analisis data dalam penelitian ini adalah uji normalitas, uji homogenitas. Uji independent sampet-tes dan uji regeresi linear sederhana. Hasil penelitian menunjukkan : 1) terdapat perbedaan model pembelajaran picture and picture berbantuan flash card terhadap pemahaman konsep rantai makanan siswa dengan nilai signifikan 0.016<0,05 dan 0,015<0,05; 2) terdapat pengaruh penggunaan model pembelajaran picture and picture berbantuan flash card terhadap pemahaman konsep rantai makanan siswa dengan taraf signifikansi 0,006 < 0,05. Maka dapat disimpulkan bahwa model pembelajaran picture and picture berbantuan flash card berpengaruh terhadap pemahaman konsep rantai makanan.Kata kunci : flash card, pemahaman konsep, picture and picture